Studies on the Immune Response to Amblyomma Variegatum in Cattle and the Effects of Haemoparasitism on The Acquisition of Tick Resistance - Dossa, S.C. (University of Ghana, 1995)
Acaricides in tick control, had been thought to be in Africa the panacea for over a century. Environmental and economic constraints, development of acaricide-resistant strains due to acaricide misuse, have brought about the need for an alternative tick control strategy. The use of tick resistant cattle has then been advocated and echoed in the USA and Australia where it got its full expansion. In Africa, few works have been undertaken on tick resistance despite the fact that many tick species are found on the continent. Studies on acquisition of immunity to tick and especially to A. variegatum in Africa are very scarce so several questions need to be answered before the use of such a method. Therefore, an attempt was made to shed some lights on the tick-cattle interactions and on some of the factors which could influence the acquisition of resistance. We have chosen the Boran cattle-A variegatum model. That model was compared to those of A. variegatum-Ayrshire cattle and A. variegatum-crossbred Friesian x Boran. The resistance was artificially induced by applying simultaneously at one month interval, 100 nymphs on one ear and 20 males and 20 females on the other ear. At the beginning of the experiment the average age of the 20 animals was one year. For the first time, the status of acquired resistance was assessed with a multivariate analysis method. The principal component analysis (PCA) and fastclus procedure (SAS/STAT) were performed on the variables with high loads. It was noticed after the first infestation that, all the biological parameters favoured tick survival. The percentage engorged (PENGD), the percentage dead (PDEAD), the feeding period (FPR), the engorgement weight (ENGWT), the percentage that moulted (PMLTD) and the percentage that engorged above critical weight (PEACWT), with loads > 0.45 proved to be the indicators for the resistance to nymphs and adults. Three groups (high, moderate, low) of resistance have been defined using the fastclus procedure. Each group has been subdivided into three lots with two individuals each. The resistance dynamic was assessed using the ANOVA procedure. It was observed with the Boran cattle that resistance to the nymphs was already induced from the third infestation. Resistance to adults did not show a defined trend. A decline in the immunity level to nymphal and adult stage was observed from the 4th and 5th infestation. In order to assess the effects of trypanosomosis or babesiosis on the acquired immunity, the tick-immune animals from the above lots were infected separately with either 1 ml of 107 blood stream T. congolense or with 150 ml of infective blood from an immunosuppressed donor calf bearing 10% B. bigemina parasites. The same number of ticks was applied, in the same manner at the height of parasitaemia. There was a significant decrease in the PENGD, ENGWT, PMLTD, PEACWT, and a significant increase in the PDEAD and the FPR which indicated an increase in the resistance status. Acquired resistance to A. variegatum could also be demonstrated in the purebred Bos taurus Ayrshire as well as in the crossbred Bos indicus (Boran) x Bos taurus (Friesian) cattle, after four to five successive infestations though some individual variations could also be noticed. acquired by crossbred Friesian x Boran and Ayrshire revealed that, the crossbred acquired significantly higher immunity than the other two breeds after the first two infestations. Although relatively lower, the resistance acquired by the Ayrshire was not significantly different from that of the Boran. The profile of gel filtration chromatography of the tick-immune serum obtained from the Boran cattle showed 3 peaks corresponding to IgM, IgGs, and albumins. The IgGs run through affinity chromatography using protein ASepharose 4BR, showed two peaks corresponding to the lgG1 and lgG2 fractions. The silver-stained profile revealed the heavy and light chains respectively around 54kDs and 29kDs while the IgM fraction showed three different bands of 77kDs, 69kDs and 29kDs. SDS-PAGE gels of saliva and salivary gland homogenates, sequentially prepared from the ticks, showed that different molecules were injected into the host during attachment and feeding. Several molecules were recognized by the whole tick-immune serum as well as by the lgG1 and lgG2 obtained after fractionation and purification through gel filtration chromatography and gel affinity chromatography and the immunoblotting procedure. Quantification of the antibodies implicated in the acquired immunity by indirect and direct ELISA showed that lgG1 was present and correlated with some of the parameters used to assess the acquisition of resistance. A higher host antibody concentration was observed after the sixth infestation when ticks were fed on the haemoprotozoan-infected animals. The IgM concentration remained unchanged during the infestations denoting its passive role in the mechanism of acquired immunity.
Thesis(PhD)-University of Ghana,1995.